2016
DOI: 10.1016/j.taap.2016.05.001
|View full text |Cite
|
Sign up to set email alerts
|

The role of hepatocyte nuclear factor 4-alpha in perfluorooctanoic acid- and perfluorooctanesulfonic acid-induced hepatocellular dysfunction

Abstract: Perfluorooctanoic acid (PFOA) and perfluorooctanesulfonic acid (PFOS), chemicals present in a multitude of consumer products, are persistent organic pollutants. Both compounds induce hepatotoxic effects in rodents, including steatosis, hepatomegaly and liver cancer. The mechanisms of PFOA- and PFOS-induced hepatic dysfunction are not completely understood. We present evidence that PFOA and PFOS induce their hepatic effects via targeting hepatocyte nuclear factor 4-alpha (HNF4α). Human hepatocytes treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 77 publications
5
70
0
Order By: Relevance
“…Recently, the European Food Safety Authority (EFSA) reported that the positive association of perfluorooctane sulfonate (PFOS) and perfluorooctanoic acid (PFOA), the two most common PFASs, with total cholesterol serum levels, as observed in several studies, may result from a possible common reabsorption of bile acids, PFOS, and PFOA from the gut and shared membrane transport pathways into the liver (https:// www.efsa.europa.eu/sites/default/files/news/efsa-contam-3503.pdf). Interestingly, it has been hypothesized that 7-alphahydroxylase (CYP7A1), which catalyzes the first and ratelimiting step in the formation of BAs from cholesterol, may be downregulated by PFASs [9,10]. This may lead to increased re-uptake of BAs, which would generate negative feedback loops via the farnesyl-X-receptor and subsequently reduce their de novo synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the European Food Safety Authority (EFSA) reported that the positive association of perfluorooctane sulfonate (PFOS) and perfluorooctanoic acid (PFOA), the two most common PFASs, with total cholesterol serum levels, as observed in several studies, may result from a possible common reabsorption of bile acids, PFOS, and PFOA from the gut and shared membrane transport pathways into the liver (https:// www.efsa.europa.eu/sites/default/files/news/efsa-contam-3503.pdf). Interestingly, it has been hypothesized that 7-alphahydroxylase (CYP7A1), which catalyzes the first and ratelimiting step in the formation of BAs from cholesterol, may be downregulated by PFASs [9,10]. This may lead to increased re-uptake of BAs, which would generate negative feedback loops via the farnesyl-X-receptor and subsequently reduce their de novo synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…The method presented here is suitable for fast, automated analysis of PFAS and BAs from human serum, and the sample amount can be reduced to 20 µL, however, with some loss of sensitivity. and NTCP are based on literature [12,8,26,19]. Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple MDCs can disrupt hepatic function, leading to toxicity, altered gluconeogenesis, and impaired glycogen storage, including POPs [62], BPA [63,64], PCBs [65], perfluorooctanoic acid (PFOA) [66], atrazine [67], arsenic [68], and DEHP [69]. For example, rats exposed to lipophilic POPs contained in dietary fish oil exhibited insulin resistance, abdominal obesity, and hepatosteatosis [62].…”
Section: Disruption Of Insulin Actionmentioning
confidence: 99%
“…TCDD), and polyphenols [70]; thus, it is a likely mediator of MDC toxicity. Interestingly, RNA-Seq analysis of human hepatocytes exposed to PFOA and PFOS demonstrate altered expression of lipid metabolism genes, possibly by direct interference with and downregulation of hepatocyte nuclear factor 4α (HNF4α), a master regulator of hepatocyte development and metabolism [66]. Mutations in HNF4α also cause a form of familial diabetes, maturity onset diabetes of the young type 1 (MODY1), which is uniquely responsive to the insulin augmenting class of sulfonylurea drugs.…”
Section: Disruption Of Insulin Actionmentioning
confidence: 99%